2008
DOI: 10.1038/bjp.2008.257
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated cholecystokinin is more potent in inducing anorexia than conditioned taste aversion in rats

Abstract: Background and purpose: The physiological involvement of endogenous cholecystokinin (CCK) in the termination of feeding has been challenged by evidence of aversive effects of exogenous CCK 8 . We previously prolonged the anorectic effect of CCK by conjugation to polyethylene glycol (PEGylation) to produce PEG-CCK 9 . In this study, we investigated the ability of different doses of PEG-CCK 9 to induce conditioned taste aversion (CTA) and satiety and identified the receptors involved in CTA induction. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In agreement, circulating glucose and insulin were almost identical to saline-treated control mice, indicating lack of detrimental metabolic effects despite significantly lowered body weights. These observations accord with other studies using longer-acting CCK agonists, where the occurrence of adverse effects such as intestinal discomfort, tolerance, and conditioned taste aversion was atypical and dose related (Verbaeys et al 2008(Verbaeys et al , 2009a. The finding in one study of pancreatic hyperplasia and, in some cases, pancreatitis in rats treated with a long-acting PEGylated version of CCK-9 for 14 days (Verbaeys et al 2009a) was not replicated in previous investigations with (pGlu-Gln)-CCK-8, where amylase and lipase levels were actually reduced (Irwin et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement, circulating glucose and insulin were almost identical to saline-treated control mice, indicating lack of detrimental metabolic effects despite significantly lowered body weights. These observations accord with other studies using longer-acting CCK agonists, where the occurrence of adverse effects such as intestinal discomfort, tolerance, and conditioned taste aversion was atypical and dose related (Verbaeys et al 2008(Verbaeys et al , 2009a. The finding in one study of pancreatic hyperplasia and, in some cases, pancreatitis in rats treated with a long-acting PEGylated version of CCK-9 for 14 days (Verbaeys et al 2009a) was not replicated in previous investigations with (pGlu-Gln)-CCK-8, where amylase and lipase levels were actually reduced (Irwin et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…We therefore previously investigated the ability of PEG-CCK 9 to induce a conditioned taste aversion (CTA). We demonstrated that PEG-CCK 9 induces both satiety and CTA and that both effects increase with dose [37]. A dose of 8 mg kg À1 was the minimal effective dose to produce CTA.…”
Section: Discussionmentioning
confidence: 72%
“…A dose of 8 mg kg À1 was the minimal effective dose to produce CTA. However, even at this dose, the PEGylated conjugate is more potent in inducing satiety, suggesting that the anorexia cannot be completely attributed to the aversiveness of the drug [37]. Experiments using smaller doses of PEG-CCK 9 and thus inducing a lesser degree of aversiveness, might be useful to unravel the contribution of the PEG-CCK 9 -induced CTA in the observed lack of tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…tractus solitarius (NTS; a CNS region crucial for integrating gutderived prandial signals and promoting meal termination) (Beutler et al, 2017;Blouet and Schwartz, 2012;D'Agostino et al, 2016;Hayes, 2009, 2012;Hayes et al, 2011Hayes et al, , 2016aHayes et al, 2010Hayes et al, , 2016b) also contains Calcr cells (Calcr NTS neurons). Importantly, while agonists for CALCR (and other gut peptide receptors) decrease food intake, they also produce aversive responses that mimic gut malaise (Adams et al, 2018;Halatchev and Cone, 2005;Schier et al, 2012;Verbaeys et al, 2008), potentially limiting their therapeutic utility.…”
Section: Context and Significancementioning
confidence: 99%